The innovation delusion - Vinsel, Lee; Russell, Andrew L. (New York: Currency, 2020)
"or forty years, innovation has been the hottest buzzword in business. But what if the benefits of innovation have been exaggerated, and our obsession with the new has distracted us from the work that matters most? It's hard to avoid innovation these days. Nearly every product gets marketed as being disruptive, whether it's a new technology or a new toothbrush. But in this manifesto on the state of American work, historians of technology Lee Vinsel and Andrew Russell argue that our focus on shiny new things has made us poorer, less safe, and--ironically--less innovative. Drawing on years of original research and reporting, Russell and Vinsel show how our fixation on innovation has harmed every corner of the economy. Corporations have spent millions hiring chief innovation officers while their core businesses tanked. Computer science programs have focused on programming and development even though the overwhelming majority of jobs are in IT and maintenance. Suburban sprawl has saddled cities with expensive infrastructure and piles of deferred maintenance that they can't afford to fix. And sometimes, innovation even kills--like in 2018, when a Miami bridge hailed for its innovative design collapsed onto a highway and killed six people. Vinsel and Russell tell the at-times humorous, at-times alarming story of how we devalued the work that keeps our world going--and in so doing, wrecked our economy, left our public infrastructure derelict, and lined the pockets of consultants who combine the ego of Silicon Valley with the worst of Wall Street's greed. They offer a compelling plan for how we can shift our focus in resources away from the pursuit of growth at all costs, and back toward the people and technologies underpinning so much of modern life. For anyone concerned by the crumbling state of our roads, bridges, and airports, and the direction our economy is headed, The Innovation Delusion is a deeply necessary re-evaluation of a trend we can still disrupt"--
Includes bibliographical references and index.
Keywords: Technological innovations; Technological innovations; New products; Social responsibility of business; Sustainable development